Updates of Scleroderma (Basidiomycota, Boletales): new data from 18 selected species in China - Yang, Kun L.; Lin, Jia Y.; Li, Guang-Mei; Yang, Zhu L. (Phytotaxa, 2025)
To bring new data for taxonomy of the common but insufficiently known genus Scleroderma, we have performed morphological and phylogenetic studies on 63 relevant collections gathered across China. Three previously described sections of Scleroderma, namely sect. Scleroderma, sect. Sclerangium and sect. Reticulatae, are accepted with revisions from the current phylogenies and observations. Peridium thickness, morphology of basidiospore ornamentation, and the presence or absence of clamp connections, are found to be informative characteristics for distinguishing these sections. A total of 18 species belonging to these three sections are identified and described, wherein nine are new to science (S. boluoshanense, S. gaibeioides, S. lunare, S. navigatum, S. pernicococcum, S. plutonium, S. solare, S. zengchengense and S. zijinshanense), three are newly recorded in China (S. capeverdeanum, S. nastii and S. xanthochroum), and six are previously known in China (S. areolatum, S. bovista, S. cepa, S. suthepense, S. venenatum and S. yunnanense). The edibility/toxicity of analysed species seems largely consistent with our phylogenies. Most of the species inferred as poisonous are found to be nested in the sect. Scleroderma, while safer species are found within the sect. Sclerangium. However, it must be noted that credible molecular evidence for many species inferred as edible is largely absent, and thus they require further confirmations for the sake of safety. The phylogenetic position of sect. Caloderma and S. dictyosporum remains uncertain, due to the lack of more samples.